A waste incineration flue gas desulfurization system and method based on oxidation absorption
Patent Information
- Application Number
- CN202611393494.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-30
AI Technical Summary
[0009]本发明的一个目的在于提供一种基于氧化吸收的垃圾焚烧烟气脱硫系统及方法,通过催化氧化体系与电化学原位再生,实现SO2的高效脱除与吸收液活性组分的持续再生,解决现有氧化吸收脱硫技术中氧化剂消耗量大、催化剂循环效率低、无法适应垃圾焚烧烟气复杂工况等技术问题
[0045]本发明实现了吸收液中主氧化剂(S2O82-)、辅助氧化剂(H2O2)和催化剂(Fe2+)的原位再生。系统运行过程中,仅需少量补充多齿络合剂及电能,无需持续外购和投加过硫酸钠、双氧水和铁盐,实现了烟气脱硫过程的绿色、低碳与闭环循环。
Smart Images

Figure CN122998947A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of flue gas purification, specifically to a waste incineration flue gas desulfurization system and method based on oxidation absorption. Background Technology
[0002] Waste-to-energy incineration is an important way to reduce, render harmless, and recycle municipal solid waste. However, the flue gas produced during waste incineration contains large amounts of pollutants such as SO2, HCl, HF, dioxins, and heavy metals. Among these, SO2 is a major precursor to acid rain and air pollution and must be strictly removed before it can be emitted.
[0003] Currently, flue gas desulfurization for waste incineration mainly utilizes mature technologies from coal-fired power plants, including limestone-gypsum wet process, semi-dry rotary spray process, and dry circulating fluidized bed process. Among these, the limestone-gypsum wet process is widely used due to its high desulfurization efficiency (>95%) and stable operation. However, this technology has the following inherent defects: (1) it generates a large amount of desulfurization gypsum solid waste, which has high disposal costs and poses a risk of secondary pollution; (2) the pH of the absorbent needs to be maintained above 5.5, which places strict requirements on equipment corrosion and scaling control; (3) it can only achieve the phase transfer of SO2 from the gas phase to the solid phase, and cannot achieve the recycling of sulfur resources.
[0004] Furthermore, existing technologies consume large amounts of oxidants and have high operating costs. H2O2 is a disposable consumable that needs to be continuously purchased and replenished. Under conditions where the SO2 concentration in waste incineration flue gas flues widely, the amount of H2O2 added is difficult to control precisely, leading to waste of reagents or incomplete oxidation.
[0005] Meanwhile, under near-neutral conditions at pH 4.0–6.0, Fe 2+ It is easily oxidized to Fe 3+ The iron salts hydrolyze and precipitate as Fe(OH)3, leading to catalyst deactivation and system scaling. Although the addition of multi-toothed complexing agents such as EDTA can inhibit Fe precipitation to some extent, the reduction and regeneration rate is much lower than the formation rate, causing catalytic cycle breakage and requiring frequent replenishment of fresh iron salts.
[0006] The active component (Fe) in the absorbent of the existing oxidation absorption process 2+ (H2O2, persulfate) are continuously consumed during the desulfurization process and cannot be regenerated in situ, resulting in the system's inability to operate stably for a long time.
[0007] Waste incineration flue gas is characterized by high chlorine levels, high dust levels, and drastic fluctuations in SO2 concentration. - It exhibits strong coordination poisoning effect on Fe-based catalysts, and at high concentrations, it can cause chlorine evolution side reaction at the electrochemical anode, reducing current efficiency.
[0008] Therefore, there is an urgent need to develop a new desulfurization method that can achieve closed-loop regeneration of the active components of the absorbent, adapt to the complex operating conditions of waste incineration flue gas, and combine high desulfurization efficiency with low operating costs. Summary of the Invention
[0009] One objective of this invention is to provide a waste incineration flue gas desulfurization system and method based on oxidation absorption. By using a catalytic oxidation system and electrochemical in-situ regeneration, it achieves efficient removal of SO2 and continuous regeneration of the active components of the absorbent, thus solving the technical problems of existing oxidation absorption desulfurization technologies, such as high oxidant consumption, low catalyst circulation efficiency, and inability to adapt to the complex operating conditions of waste incineration flue gas.
[0010] The first objective of the invention is a method for desulfurizing waste incineration flue gas based on oxidation absorption, comprising the following steps:
[0011] Step 1: Rapidly cool the flue gas from waste incineration to 70-90°C;
[0012] The temperature of raw flue gas discharged from waste incinerators is typically between 180 and 250°C. This invention rapidly reduces the flue gas temperature to 70-90°C using a quench tower. This avoids damage to the packing material and electrochemically sensitive components in the subsequent absorption tower caused by the high-temperature flue gas. Furthermore, 70-90°C falls within the optimal temperature range for the synergistic activation of persulfate and Fe catalytic activation, which is beneficial for subsequent oxidation reactions. Higher temperatures promote the thermal activation of persulfate and accelerate the oxidation of SO4·4·4·°C. - The generation of free radicals; on the other hand, the solubility of SO2 in water decreases with increasing temperature (the saturated solubility of SO2 at 70℃ is about 0.5 g / L, which is significantly lower than about 10 g / L at room temperature), which is not conducive to the gas-liquid mass transfer of SO2. The present invention controls the temperature in the range of 70~90℃ based on the following comprehensive considerations: (1) This temperature range is the lower limit temperature range in which the thermal activation of persulfate is significantly effective, and the contribution of thermal activation decreases sharply below 70℃; (2) Although high temperature reduces the equilibrium solubility of SO2, the strong oxidizing free radicals in the absorption liquid of the present invention can quickly dissolve the SO2 (in the form of HSO3) - (Existing in its original form) oxidized to SO4 2- This makes HSO3 in the liquid phase - The concentration is always maintained at an extremely low level, thereby generating a continuous concentration gradient driving force, which causes SO2 to continuously dissolve from the gas phase into the liquid phase, effectively overcoming the adverse effects of reduced equilibrium solubility at high temperatures; (3) If the temperature of the waste incineration flue gas is too low (<70℃) after rapid cooling, a large amount of water vapor in the flue gas will condense in the subsequent equipment, causing equipment corrosion and excessive dilution of the absorbent. Therefore, 70~90℃ is the optimized temperature range that comprehensively considers oxidation kinetics, gas-liquid mass transfer kinetics and equipment corrosion prevention requirements.
[0013] Step 2: The cooled flue gas is sprayed and washed with alkaline solution to remove fly ash and acidic gases, and the Cl content in the washed flue gas is controlled. - With a concentration <500 mg / L, pre-washed flue gas was obtained;
[0014] Waste incineration flue gas contains large amounts of HCl, HF, and fly ash particles. This step involves spraying with NaOH or Ca(OH)2 alkaline solution to remove most of the HCl, HF, and fly ash. The key control indicator is the Cl content in the flue gas after scrubbing. - Concentration <500 mg / L. Cl - Exceeding this concentration limit will cause two kinds of harm: Cl - with Fe 2+ / Fe 3+ [FeCl4] is formed. 2- [FeCl3(H2O)] - Chloride complexes such as FeCl2(H2O)2 have thermodynamic stability constants on the same order of magnitude as Fe-EDTA / Fe-EDDS complexes, and are found in high Cl2 concentrations. - At certain concentrations, it competitively displaces the coordination sites of multidentate complexing agents, leading to a decrease in the effective concentration of Fe-based catalysts and a reduction in catalytic cycle rate.
[0015] Step 3: The pre-washed flue gas passes through the main absorption tower from bottom to top, sequentially passing through the bubbling oxidation reaction section, the packed absorption section, and the spray washing section. The absorbent liquid flows from the main absorption tower, sequentially through the spray washing section and the packed absorption section, into the absorption oxidation liquid layer of the bubbling oxidation reaction section. This dissolves the SO2 in the flue gas in the absorbent liquid, and the active components in the absorbent liquid, namely the sulfate free radicals (SO4•-) generated by persulfate and hydrogen peroxide under Fe²⁺ catalysis, are absorbed. - ) and hydroxyl radicals (·OH) are oxidized in situ to SO4. 2- The flue gas is purified.
[0016] The bubbling oxidation reaction section is located at the bottom of the main absorption tower, maintaining a pre-set height of absorbent oxidation liquid layer inside. The pre-washed flue gas is dispersed into microbubbles with an average diameter ≤3mm by a gas distributor submerged in the liquid layer and enters the liquid phase. This section serves as the main reaction zone of the system, bearing the majority of the SO2 removal load. The microbubbles rise slowly in the liquid layer at a depth of 0.8–2.0m with an apparent gas velocity of 0.05–0.15m / s and a residence time ≥5s, providing sufficient contact time for gas-liquid mass transfer and liquid-phase oxidation reaction. In this liquid phase section, dissolved SO2 is rapidly converted to HSO3. - And in the absorption liquid, •OH and SO4• - It is rapidly oxidized to SO4 under the synergistic effect of two free radicals. 2- The main reaction pathways include: HSO3- The hydrogen atom is removed by •OH to form SO3• - Intermediate, SO3• - It combines with dissolved oxygen to form persulfate radicals (SO5•). - SO5• - Further with HSO3 - A chain reaction occurs to produce SO4• - and SO4 2- This allows SO2 to be converted into stable sulfates.
[0017] The packing absorption section is positioned above the bubbling oxidation reaction section and contains at least two sections of oxidation-resistant modified packing. This is because the absorbent in this system contains high concentrations of •OH and SO4• - H2O2 and S2O8 2- For components with equal oxidizing power, conventional polypropylene or polyvinyl chloride packings are prone to oxidation, chain breakage, surface pulverization, and loss of hydrophilicity during long-term operation. Therefore, this invention selects surface-modified hydrophilic polytetrafluoroethylene, polyvinylidene fluoride, or silicon carbide packings to ensure the structural stability and liquid film spreading performance of the packings under high oxidation potential environments. An annular groove-type liquid redistribution structure is provided between two adjacent oxidation-resistant modified packing layers to collect the liquid flow gathered at the bottom of the upper packing layer and redistribute it evenly to the top surface of the lower packing layer. This eliminates liquid flow segregation and channeling phenomena caused by the tower wall effect, ensuring that the gas and liquid phases maintain a uniform countercurrent contact state across the entire tower cross-section.
[0018] The spray scrubbing section is located above the packing absorption section and serves as the final unit for purifying flue gas. The spray scrubbing section is equipped with spray layers for washing the flue gas. The spray layers consist of a first spray layer, a second spray layer, and a third spray layer arranged sequentially from bottom to top.
[0019] The first spray layer uses a high-pressure solid cone nozzle to form a droplet cluster with an average particle size of 100-200 μm under a spray pressure of 0.3-0.5 MPa. The inertia of the larger droplets is used to capture the residual high concentration of SO2 in the flue gas. The second spray layer uses a swirling nozzle with an average droplet size of 80-150 μm. The swirling number of the nozzle is 0.6-2.0, and the tangential velocity component at the nozzle exit is 8-25 m / s. In the initial stage after leaving the nozzle, the droplets carry the tangential velocity component, forming a spiral diffusion trajectory in the flue gas, significantly increasing the collision frequency and effective contact area between the droplets and the flue gas. The swirling number is defined as the ratio of the tangential moment of momentum to the axial moment of momentum at the nozzle exit, and is a dimensionless parameter characterizing the intensity of the swirling flow. The third spray layer uses a low-pressure fine atomizing nozzle to form a dense liquid mist curtain with an average particle size of 50-100 μm, providing a final deep cleaning of the flue gas. The three-layer spray system, through a gradient combination of decreasing particle size and fluid dynamic behavior, ensures that the SO2 concentration in the outlet flue gas remains consistently below 35 mg / Nm³. 3At the same time, it effectively controls the amount of liquid entrainment.
[0020] On the other hand, in step 4, the electrochemical regeneration unit includes an electrolytic cell divided into an anode chamber and a cathode chamber by an ion exchange membrane; the absorbent enters the anode chamber and the cathode chamber respectively, and after the reaction, they merge and return to the main absorption tower; the anode chamber is equipped with a high oxygen evolution overpotential anode, the cathode chamber is equipped with a carbon-based cathode, and the bottom of the cathode chamber is provided with a microporous aeration disc.
[0021] The anode comprises one of a boron-doped diamond electrode, a Ti / SnO2-Sb electrode, or a Ti / PbO2 electrode; the cathode comprises one of a graphite felt, a carbon felt, or a carbon nanotube-modified electrode. Oxygen-containing gas, specifically oxygen-enriched air with an oxygen volume fraction of 25%–40%, is continuously introduced into the cathode chamber of the electrochemical regeneration unit. The oxygen-containing gas is introduced through a microporous aeration disc at the bottom of the cathode chamber, with the apparent gas velocity controlled at 0.5–3.0 cm / s.
[0022] During the electrochemical regeneration process, an oxidation reaction occurs in the anode chamber, producing SO4. 2- Transformed into S2O8 2- A reduction reaction occurs in the cathode chamber, where O2 is converted to H2O2 and Fe... 3+ Reduced to Fe 2+ If the products from the cathode and anode come into direct contact, the H2O2 generated at the cathode will be oxidized and decomposed by the anode, while the S2O8 generated at the anode will be decomposed. 2- It will be reduced at the cathode, reducing current efficiency. This invention uses an ion exchange membrane, preferably a cation exchange membrane or a bipolar membrane, to physically isolate the two chambers, allowing only specific ions, such as H⁺ or Na⁺, to migrate directionally to maintain charge balance, thus preventing cross-contamination of products from the anode and cathode. The design of the absorbent flowing separately into the two chambers and then converging after the reaction ensures a sufficient supply of substrate to each chamber while also allowing the regenerated S₂O₈ to be reduced. 2- H2O2 and Fe 2+ After merging, the mixture is quickly combined and then directly returned to the main absorption tower to participate in the desulfurization and oxidation cycle, simplifying the process flow.
[0023] Furthermore, the absorbent comprises the following components in parts by weight: 2.4 to 24.0 parts sodium persulfate, 0.17 to 1.70 parts hydrogen peroxide, 1.4 to 14.0 parts ferrous sulfate heptahydrate, and 3.7 to 18.6 parts multidentate complexing agent; the pH value of the absorbent is 4.0 to 6.0.
[0024] The multidentate complexing agent is EDTA or EDDS; when the multidentate complexing agent is EDTA, its weight fraction is 3.7~14.8 parts; when the multidentate complexing agent is EDDS, its weight fraction is 4.5~18.6 parts; the multidentate complexing agent and Fe 2+ The molar ratio is 1:1 to 2:1.
[0025] Sodium persulfate (Na2S2O8) serves as the primary oxidant, and under the catalysis of transition metal ions, it can generate sulfate radicals (SO4•-) with higher oxidation potential (2.5~3.1V) and longer half-life. - Hydrogen peroxide (H2O2) is used as an auxiliary oxidant, primarily to generate hydroxyl radicals (•OH).
[0026] Sodium persulfate (Na2S2O8) and hydrogen peroxide (H2O2) are combined to construct SO4• - A system of two free radicals coexisting with •OH. SO4• - It exhibits extremely high selective oxidation rates for electron-rich sulfur-containing compounds, while •OH possesses a broad-spectrum, non-selective oxidation capability. The amount of hydrogen peroxide added is controlled at a low level because it mainly acts as an initiator and synergist. Excessive addition not only increases operating costs but also causes H2O2 to become a free radical quencher, resulting in ineffective decomposition and reducing overall oxidation efficiency.
[0027] Ferrous sulfate heptahydrate provides Fe 2+ As a homogeneous catalyst, it is used to activate persulfate and hydrogen peroxide. 2+ With S2O8 2- The reaction produces SO4• - and Fe 3+ At the same time, Fe 2+ It reacts with H2O2 to produce •OH and Fe. 3+ Iron salt catalysts are widely available, inexpensive, and environmentally friendly. Their dosage range is stoichiometrically matched with the oxidant dosage, ensuring that the catalytic activation rate is compatible with the SO2 absorption rate. This avoids oxidant accumulation due to insufficient catalyst or self-quenching effects of free radicals caused by excessive catalyst.
[0028] In the weakly acidic environment of pH 4.0~6.0 required for flue gas desulfurization, free Fe... 2+ and Fe 3+ It readily hydrolyzes to form ferric hydroxide precipitate, leading to catalyst deactivation and packing blockage. Introducing a multidentate complexing agent (EDTA or EDDS) utilizes its abundant coordinating atoms (nitrogen, oxygen) to form highly stable water-soluble chelates with iron ions (such as [Fe(II)-EDTA)). 2- This method locks iron ions in the solution, solving the problem that traditional oxidation technologies must operate under strongly acidic conditions (pH 2.5~3.5). It allows the absorbent to maintain extremely high catalytic activity within a wide pH window of 4.0~6.0. This not only avoids severe corrosion of the equipment under strong acid conditions but also eliminates the need for frequent pH adjustments before and after the flue gas enters and exits the tower, significantly reducing acid and alkali consumption.
[0029] EDDS (especially the [S,S]-EDDS isomer) is a green, biodegradable alternative to EDTA. Because the molecular weight of EDDS (approximately 350 g / mol) is slightly larger than that of EDTA (approximately 292 g / mol), and both react with Fe... 2+ There are slight differences in the complexation stability constants of the EDDS. To achieve the same molar complexation concentration and catalytic stability, the weight fraction of EDDS needs to be increased accordingly.
[0030] EDTA is cheaper and has a strong complexing ability, making it suitable for cost-sensitive routine projects; EDDS, on the other hand, has excellent biodegradability, which can eliminate the risk of environmental accumulation when waste absorbent is discharged, making it suitable for areas with extremely high environmental protection requirements.
[0031] Both EDTA and EDDS are hexadecantal ligands, and theoretically, 1 mole of ligand can completely complex 1 mole of Fe. 2+ Setting the lower limit of the molar ratio to 1:1 ensures that all iron ions are effectively encapsulated, preventing the precipitation of free iron; setting the upper limit to 2:1 utilizes excess ligands as a buffer to competitively bind trace heavy metal impurities (such as Pb) that may be introduced into the flue gas. 2+ Cd 2+ The presence of either a free complexing agent or a competing anion is used to prevent them from poisoning the catalyst. Simultaneously, limiting the ratio to 2:1 is to prevent excessively high concentrations of free complexing agents from consuming free radicals within the system (the complexing agent itself can also be oxidized and degraded by •OH), thereby optimizing reagent costs while ensuring catalytic stability.
[0032] pH value (4.0~6.0) is the optimal thermodynamic and kinetic equilibrium point between the stability of metal complexes and the yield of free radicals.
[0033] At pH > 6.0, even in the presence of complexing agents, Fe 3+ It also tends to form hydroxyl complex precipitates; at pH < 4.0, H + Excessive concentration can alter the protonation state of the complex, reducing its stability, and an overly acidic environment can accelerate equipment corrosion; SO2 dissolves in water to form HSO3. - It dominates in the pH range of 4.0 to 6.0, while HSO3 - It is SO4• - The most sensitive substrate for free radical oxidation, this pH range maximizes the synergistic effect of gas-liquid mass transfer driving force and liquid-phase oxidation reaction rate.
[0034] Furthermore, the bubbling oxidation reaction section is located at the bottom of the main absorption tower. The bubbling oxidation reaction section contains an absorption oxidation liquid layer of a predetermined height. The bubbling oxidation reaction section includes a gas distributor immersed in the absorption oxidation liquid layer. The gas distributor includes a microporous distributor and a macroporous distributor arranged sequentially from top to bottom, forming a two-stage bubble control process of coarse bubble pre-dispersion and microbubble fine dispersion. The macroporous distributor has a larger pore size, typically 5-10 mm, and its function is to initially disperse the high-speed flue gas entering the bottom of the tower into a larger bubble group, reducing the local kinetic energy of the gas and preventing the airflow from directly impacting the microporous distributor and causing excessively high local gas velocity. The microporous distributor has a smaller pore size, typically 0.5-2 mm, further cutting the pre-dispersed airflow into microbubbles with an average diameter ≤3 mm, achieving refined control of the gas-liquid contact interface.
[0035] The depth of the absorption oxidizing liquid layer in the bubbling oxidation reaction section is 0.8~2.0m. The specific surface area of the microbubbles, i.e., the gas-liquid contact area provided by a unit volume of gas, is inversely proportional to the bubble diameter. When the bubble diameter is reduced from the conventional 5~10mm to ≤3mm, the gas-liquid specific surface area can increase by 2~3 times. At the same time, the rising velocity of the microbubbles in the liquid phase is significantly reduced, and the residence time is extended to ≥5s, providing sufficient contact and reaction time for the gas-liquid mass transfer and liquid-phase oxidation reaction of SO2.
[0036] If only a single-layer microporous distributor is used, extremely high air distribution resistance (pressure drop typically >10kPa) is required to achieve microbubbles ≤3mm, leading to a significant increase in fan energy consumption. This invention utilizes the pre-dispersion effect of a large-pore distributor to initially homogenize the airflow entering the microporous distributor. The microporous distributor only needs to perform fine dispersion, and its air distribution resistance can be controlled at 3~5kPa, reducing system operating energy consumption.
[0037] Trace amounts of dust, droplets, or precipitates in the absorbent liquid that may be carried in the flue gas can easily deposit in the tiny pores of the microporous distributor, causing pore blockage. The macroporous distributor, acting as a pre-barrier, can intercept most particles and droplets, and its larger pore size makes it less prone to clogging, thus protecting the microporous distributor. Furthermore, the airflow disturbance zone formed between the two distributor stages can promote the suspension and redispersion of particles, reducing the risk of deposition.
[0038] The larger bubbles generated by the large-pore distributor create strong liquid-phase turbulence during their ascent, forming a composite flow field structure of large-scale circulation and small-scale micro-mixing with the micro-bubble group generated by the micro-pore distributor. This effectively eliminates the dead zone at the bottom of the tower, ensuring that the absorbent maintains a uniform concentration and temperature distribution across the entire bubbling section, and avoiding local oversaturation or incomplete reaction.
[0039] Furthermore, the absorber section is provided with at least two oxidation-resistant modified filler layers, and an annular groove liquid redistribution structure is provided between two adjacent oxidation-resistant modified filler layers; the oxidation-resistant modified filler layer includes one of the following: surface-hydrophilic modified polytetrafluoroethylene filler, polyvinylidene fluoride filler, or silicon carbide filler.
[0040] The absorbent in this system contains high concentrations of •OH and SO4• - H2O2 and S2O8 2- The strong oxidizing components have redox potentials as high as 2.5~3.1V, which places stringent requirements on the chemical stability of the filler material. Under such strong oxidizing conditions, the CH and CC bonds in the molecular chains of conventional polypropylene (PP) or polyvinyl chloride (PVC) fillers are easily attacked by free radicals, resulting in oxidative chain breakage. This leads to powdering, brittleness, and loss of hydrophilicity on the filler surface, and it usually fails within a few months, seriously affecting the gas-liquid mass transfer efficiency and the long-term stable operation of the system.
[0041] As the liquid flows downwards through the packed absorption section, due to the tower wall effect and the uneven packing, the liquid flow gradually concentrates towards the tower wall, forming wall flow. Simultaneously, localized areas of concentrated and sparse liquid flow may appear within the packing layer, forming channeling. Wall flow and channeling significantly reduce the effective wetting area of the packing layer, leading to uneven gas-liquid contact and a marked decrease in mass transfer efficiency.
[0042] This invention incorporates an annular groove-type liquid redistribution structure between adjacent packing layers. The annular groove is circumferentially positioned along the inner side of the tower wall, and its bottom is equipped with multiple uniformly distributed guide holes or overflow weirs. Liquid flowing down from the bottom of the upper oxidation-resistant modified packing layer is first intercepted by the annular groove, preventing it from continuing to flow down the tower wall and forming wall flow. Subsequently, the liquid collects within the annular groove and is redistributed uniformly across the entire cross-section of the top surface of the lower packing layer through the guide holes or overflow weirs, eliminating channeling and restoring a uniform liquid film distribution.
[0043] Furthermore, the present invention proposes a second objective: a waste incineration flue gas desulfurization system based on oxidation absorption for implementing the above-described method.
[0044] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0045] This invention achieves the primary oxidant (S2O8) in the absorbent liquid 2- ), auxiliary oxidant (H2O2) and catalyst (Fe) 2+ In-situ regeneration of flue gas. During system operation, only a small amount of multi-toothed complexing agent and electricity are required for replenishment. There is no need to continuously purchase and add sodium persulfate, hydrogen peroxide and iron salts, thus realizing a green, low-carbon and closed-loop cycle in the flue gas desulfurization process.
[0046] This invention introduces a multi-toothed complexing agent (EDTA or EDDS) with Fe 2+ / Fe 3+ The formation of stable water-soluble chelates enables the absorbent to maintain high catalytic activity within a pH range of 4.0 to 6.0, solving the problem that traditional iron-based catalytic oxidation technology must operate under strongly acidic conditions.
[0047] This invention employs a gradient purification process consisting of a bubbling oxidation reaction section, a packing absorption section, and a spray scrubbing section. The bubbling section handles the majority of SO2 removal, the packing section provides sufficient mass transfer surface area and reaction time, and the spray scrubbing section, through the gradient coordination of three spray layers, deeply scrubs residual SO2. The SO2 concentration in the system's outlet flue gas is superior to current waste incineration flue gas emission standards. Attached Figure Description
[0048] The accompanying drawings, which are included to provide a further understanding of embodiments of the invention and form part of this application, do not constitute a limitation thereof. In the drawings:
[0049] Figure 1 A schematic diagram of the main absorption tower;
[0050] Figure 2 This is a schematic diagram of an annular trough-type liquid redistribution structure;
[0051] The attached diagram shows the markings and corresponding component names:
[0052] 1-Main absorption tower, 2-Bubble oxidation reaction section, 3-Packed absorption section, 4-Spray washing section, 5-Large pore distributor, 6-Micro pore distributor, 7-Third packing layer, 8-Second packing layer, 9-First packing layer, 10-Annular trough liquid redistribution structure, 11-First spray layer, 12-Second spray layer, 13-Third spray layer, 14-Annular trough, 15-Guide hole. Detailed Implementation
[0053] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments and accompanying drawings. However, this does not limit the invention to the scope of the embodiments described. Experimental methods in the following embodiments that do not specify specific conditions were performed according to conventional methods and conditions, or as selected according to the product instructions.
[0054] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0055] Example 1
[0056] A waste incineration flue gas desulfurization system based on oxidation absorption includes a quench tower, a pre-scrubber, and a main absorption tower 1 connected sequentially along the flue gas flow direction. The main absorption tower 1 is connected to an electrochemical regeneration unit via a circulation pipeline. The main absorption tower 1 is as follows: Figure 1 As shown, the main absorption tower 1 is divided into three sections from bottom to top: a bubbling oxidation reaction section 2, a packing absorption section 3, and a spray washing section 4.
[0057] The bubbling oxidation reaction section 2 is located at the bottom of the main absorption tower 1. The depth of the absorption oxidation liquid layer in the bubbling oxidation reaction section 2 is 0.8~2.0m. The microbubbles formed after the pre-washed flue gas passes through the gas distributor have a residence time of ≥5s in the absorption oxidation liquid layer. The bubbling oxidation reaction section 2 is equipped with an absorption oxidation liquid layer of a preset height. The bubbling oxidation reaction section 2 includes a gas distributor immersed in the absorption oxidation liquid layer. The gas distributor includes a microporous distributor 6 and a large-pore distributor 5 arranged sequentially from top to bottom. The large-pore distributor 5 is made of 316L stainless steel, with a pore diameter of 8 mm, an opening rate of 20%, and is installed at a height of 0.3m from the bottom of the tower. The microporous distributor 6 is made of silicon carbide, with a pore diameter of 1.2 mm, an opening rate of 10%, and is installed 0.2m above the large-pore distributor 5. The 0.2m distance between the two distributors forms a buffer zone for airflow disturbance.
[0058] The packing absorption section 3 is provided with a first packing layer 9, a second packing layer 8, and a third packing layer 7 arranged sequentially from top to bottom, with each packing layer being 3 m high. The packing material is polytetrafluoroethylene (PTFE) Pall rings with a surface modified by oxygen plasma hydrophilicity. An annular trough-type liquid redistribution structure 10 is provided between the two packing layers, as shown in the figure. Figure 2 As shown, it includes several concentric annular grooves 14, with several guide holes 15 of 10 mm in diameter evenly distributed at the bottom of each annular groove, and an overflow weir height of 30 mm, to ensure that the liquid is redistributed evenly to the top surface of the lower packing layer.
[0059] The spray scrubbing section 4 is equipped with spray layers for washing the flue gas. The spray layers consist of a first spray layer 11, a second spray layer 12, and a third spray layer 13 arranged sequentially from bottom to top. The first spray layer 11 is 1.0 m above the top of the packing layer, using high-pressure solid cone nozzles with a spray pressure of 0.4 MPa and an average droplet size of 150 μm. The second spray layer 12 is 0.8 m above the first spray layer, using swirling nozzles with an average droplet size of 120 μm, a swirl number of 1.2, and a nozzle outlet tangential velocity component of 15 m / s. The third spray layer 13 is 0.6 m above the second spray layer, using low-pressure fine atomizing nozzles with a spray pressure of 0.15 MPa and an average droplet size of 70 μm. A baffle-type demister is installed 1.2 m above the three spray layers, with an outlet liquid entrainment of <50 mg / Nm³.3 .
[0060] The electrochemical regeneration unit includes an electrolytic cell divided into an anode chamber and a cathode chamber by an ion exchange membrane. The electrolytic cell adopts a plate-and-frame structure, with a total of 6 groups connected in parallel. The effective electrode area of each group is 2.0 m². 2 The total effective electrode area is 12.0 m². 2 The electrode spacing is 10 mm. The anode and cathode chambers are separated by a Nafion 117 cation exchange membrane. The anode is a boron-doped diamond (BDD) electrode with a boron doping concentration of 5000 ppm; the cathode is a graphite felt electrode with a thickness of 5 mm and a specific surface area of 80 m². 2 / g. A titanium microporous aeration disc with a pore size of 50μm is installed at the bottom of the cathode chamber, through which oxygen-enriched air with an oxygen volume fraction of 30% is introduced, and the apparent gas velocity is controlled at 1.5cm / s. The absorbent is split into two chambers, each with a residence time of 45s, and after the reaction, they are combined and returned to the top spray washing section 4 of the main absorption tower 1.
[0061] Based on the above system, the flue gas treatment capacity is 5000 Nm³. 3 / h, the original flue gas SO2 concentration is 800~1200 mg / Nm 3 The HCl concentration is 400~600 mg / Nm³. 3 The fly ash concentration is 30~50 mg / Nm³. 3 The flue gas temperature is 190~220℃. This invention provides a method for desulfurizing waste incineration flue gas based on oxidation absorption, comprising the following steps:
[0062] Step 1: Rapidly cool the raw flue gas from waste incineration to 70-90°C. The raw flue gas enters the rapid cooling tower and is rapidly cooled to 80°C by water spraying. This avoids thermal damage to the subsequent PTFE packing and BDD electrode caused by high temperature, and at the same time, it makes the flue gas temperature fall into the optimal range of 70-90°C for the synergistic activation of persulfate thermal activation and Fe catalytic activation.
[0063] Step 2: After cooling, the flue gas enters the pre-scrubbing tower and is sprayed countercurrently with a 5 wt% NaOH solution at a liquid-to-gas ratio of 3 L / Nm³. 3 After washing, the HCl concentration in the flue gas decreased to <20 mg / Nm³. 3 The fly ash concentration was reduced to <5 mg / Nm³. 3 Cl - The concentration was controlled at 380 mg / L to effectively prevent Cl. - It competes with Fe-EDTA complexes for ligand substitution.
[0064] Step 3: After pre-washing, the flue gas passes through the main absorption tower 1 from bottom to top.
[0065] In the bubbling oxidation reaction section 2, the flue gas is dispersed into microbubbles with an average diameter of 2.5 mm by a double-layer gas distributor. These microbubbles rise in a 1.5 m absorbent liquid layer at an apparent gas velocity of 0.08 m / s, with a residence time of approximately 18 s. The absorbent liquid comprises the following components in parts by weight: 12.0 parts sodium persulfate, 0.85 parts hydrogen peroxide, 7.0 parts ferrous sulfate heptahydrate, and 9.3 parts EDTA; the pH of the absorbent liquid is 5.2. EDTA and Fe... 2+ The molar ratio is 1.5:1. Dissolved SO2 is rapidly converted to HSO3. - and in SO4• - •OH is oxidized to SO4 by the cooperation of two free radicals. 2- .
[0066] In the packed absorption section 3, the flue gas comes into countercurrent contact with the regenerated absorbent flowing from top to bottom, maintaining a gas-liquid specific surface area of 320 m². 2 / m 3 The above section further removes residual SO2.
[0067] In the spray washing section 4, a three-layer gradient spray washing process is used, and the SO2 concentration in the outlet flue gas is stabilized at 28~32 mg / Nm³. 3 Better than 35 mg / Nm 3 Emission standards.
[0068] Step 4: The absorbent is drawn from the bottom of the bubbling section and diverted into the electrolytic cell.
[0069] Anode chamber: SO4 2- The anode surface of the BDD is oxidized and regenerated into S2O8. 2- Current density 30 mA / cm 2 .
[0070] Cathode chamber: 30% oxygen-enriched air (O2) is introduced through a microporous aeration disc at an apparent gas velocity of 1.5 cm / s. O2 undergoes a 2e reaction on the surface of the graphite felt cathode. - ORR generates H2O2, while Fe 3+ -EDTA is reduced to Fe 2+ -EDTA.
[0071] After regeneration, the absorbent liquids merge, S2O8 2- H2O2, Fe 2+ - Once the EDTA concentration is restored to its initial value, it is directly returned to the top of the main absorption tower 1 for recycling. The system only needs to be replenished with a small amount of EDTA and electricity weekly, eliminating the need to purchase sodium persulfate, hydrogen peroxide, and iron salts.
[0072] The system was tested after 180 days of continuous and stable operation. The key operating indicators and monitoring methods are as follows:
[0073] The outlet SO2 concentration is continuously monitored online by a potentiostatic electrolysis method flue gas analyzer that meets the HJ 57-2017 standard. The sampling point is located at the center of the flue duct cross-section at the outlet of the folded-plate demister, and the instantaneous value is automatically recorded every 5 minutes. During the 180-day operation period, the fluctuation range of the outlet SO2 concentration is 28~32 mg / Nm 3 , and the arithmetic mean value is 30 mg / Nm 3 ; The desulfurization efficiency is calculated based on the synchronously online monitored inlet and outlet SO2 concentrations, and the 180-day average value is greater than 99%. The outlet liquid entrainment is measured by isokinetic sampling in the flue duct at the demister outlet according to the GB / T 13269-1991 standard. Samples are collected once a week and determined by the filter membrane gravimetric method, and the average value within 180 days is less than 50 mg / Nm 3 .
[0074] The fluctuation of Fe 2+ -EDTA concentration in the absorption liquid is determined by ultraviolet-visible spectrophotometry. Absorption liquid samples are collected daily at fixed time from the sampling port at the bottom of the bubbling oxidation reaction section, filtered through a 0.45 μm microporous membrane, the absorbance is measured at a wavelength of 258 nm and converted to concentration. The relative fluctuation percentage is calculated based on the initial concentration, and the concentration fluctuation amplitude within 180 days is less than 5%. The water contact angle of PTFE packing is measured by the sessile drop method. During the 180-day shutdown maintenance period, 5 packing samples are randomly selected from each of the three positions: the first packing layer 9, the second packing layer 8 and the third packing layer 7, and the static water contact angle is measured at room temperature using a contact angle measuring instrument. The average value of 15 measurement points is less than 40°, with no obvious deterioration compared with the initial value of 35°. The BDD electrode cell voltage is collected in real time through the high-precision DC power supply module matched with the electrolytic cell, recorded once per second. The steady-state average value during the 180-day operation period is 4.2V, with no obvious increase or fluctuation.
[0075] The anodic regeneration current efficiency of S2O8 2- and the cathodic generation current efficiency of H2O2 are both determined by iodometric titration. Samples are taken from the outlets of the anode chamber and the cathode chamber respectively. After S2O8 2- reacts with excess KI under acidic conditions to release I2, it is titrated with Na2S2O3 standard solution, and H2O2 is directly titrated with KMnO4 standard solution under acidic conditions. The current efficiency is calculated by combining Faraday's law and the actual input electric quantity, measured once a week. Within 180 days, the average anodic regeneration current efficiency of S2O8 2- is 72%, and the average cathodic generation current efficiency of H2O2 is 88%. The cathodic reduction rate of Fe 3+ is determined by measuring the concentration difference of Fe 2+ in the absorption liquid at the inlet and outlet of the cathode chamber by o-phenanthroline spectrophotometry, and dividing by the total iron concentration at the inlet. It is measured once a week, and the average value within 180 days is greater than 95%.
[0076] The power consumption per ton of flue gas desulfurization is calculated by dividing the cumulative reading of the smart meter installed in the power supply circuit of the electrochemical regeneration unit by the cumulative standard volume of the flue gas flow meter during the same period. The 180-day average is 0.012 kWh / Nm³. 3 The replenishment of reagents was double-checked using a metering pump stroke counter and a storage tank level gauge. Only EDTA needed to be replenished within 180 days, with an average weekly replenishment of 3.5 kg. No external purchase of sodium persulfate, hydrogen peroxide, or iron salts was required. Hazardous waste sludge production was measured by weighing the sludge discharged from the bottom sludge discharge port of the bubbling oxidation reaction section; the sludge discharge was zero during the 180-day operation period. During the 180-day shutdown for maintenance, the entire packing layer of the absorption section was visually and tactilely inspected to confirm that the packing was free of pulverization, brittleness, deformation, or fragmentation, and that its structural integrity was good. Regarding the selection of anode materials, boron-doped diamond (BDD) electrodes possess extremely high oxygen evolution overpotential and excellent chemical stability, making them ideal for achieving SO42- oxidation. 2- High-efficiency electrochemical oxidation to S2O8 2- Ideal anode material. Although the fabrication cost of large-area BDD electrodes is currently high, the manufacturing cost of BDD electrodes is decreasing year by year with the continuous advancement and large-scale production of hot filament chemical vapor deposition (HFCVD) technology. Furthermore, this invention can also use lower-cost Ti / SnO2-Sb electrodes or Ti / PbO2 electrodes as alternatives, although their S2O8... 2- Regenerative current efficiency is slightly lower, but its cost advantage can compensate for the efficiency loss to some extent. In practical engineering applications, the choice can be made based on the project's investment budget and operating cost requirements.
[0077] Furthermore, the electrochemical regeneration unit is designed to regenerate 40%–60% of the total oxidant consumption of the system, with the remainder being buffered and supplemented by the oxidant reserves in the absorbent system. During the initial system operation, sufficient sodium persulfate and hydrogen peroxide need to be added to establish an initial concentration reserve (total absorbent volume approximately 15–25 m³). 3 During continuous operation, electrochemical regeneration continuously replenishes the consumed oxidant, ensuring that the S2O8 in the absorbent remains constant. 2- The H2O2 concentration is maintained at a steady-state level. When the inlet SO2 concentration remains at the design upper limit for an extended period, the number of parallel electrolytic cells can be increased or the current density can be raised to improve the regeneration ratio. Under normal operating conditions, the system only requires weekly replenishment of a small amount of multi-toothed complexing agent and electrical energy, eliminating the need for continuous external purchases and additions of sodium persulfate, hydrogen peroxide, and iron salts.
[0078] Example 2
[0079] Based on Example 1, this example uses EDDS instead of EDTA as a multi-toothed complexing agent and simulates a high SO2 concentration flue gas treatment scenario under high load conditions of a waste incinerator to verify the effectiveness of the EDDS system and the system's adaptability to high load fluctuations.
[0080] Compared with Example 1, the anode of the electrochemical regeneration unit in this example uses a Ti / SnO2-Sb electrode, and the cathode uses a carbon nanotube modified electrode.
[0081] The designed flue gas treatment capacity is 5000 Nm³. 3 / h, the original flue gas SO2 concentration increased to 1800~2200 mg / Nm 3 (Simulating high-load conditions), HCl concentration is 500~700 mg / Nm³. 3 The fly ash concentration is 40~60 mg / Nm³. 3 The flue gas temperature is 200~240℃.
[0082] After the system operated continuously and stably for 180 days, the SO2 concentration at the outlet fluctuated within the range of 30~34 mg / Nm³. 3 The arithmetic mean is 32 mg / Nm 3 The desulfurization efficiency is greater than 98.5%. Fe in the absorbent liquid... 2+ The EDDS concentration fluctuated less than 6% relative to its initial value; the water contact angle of the PTFE packing was less than 42°; and the voltage of the Ti / SnO2-Sb electrode cell remained stable at 4.2 V without significant increase or fluctuation. 2- The anode regeneration current efficiency is 68%, the H2O2 cathode generation current efficiency is 85%, and the Fe... 3+ The cathode reduction rate is greater than 93%. The power consumption for flue gas desulfurization is 0.016 kWh / Nm³. 3 The only reagent replenishment is EDDS, with an average weekly replenishment of 5.2 kg. There is no need to purchase sodium persulfate, hydrogen peroxide, or iron salts. Hazardous waste sludge generation is zero. The biodegradation rate of the waste absorbent is greater than 92% after 28 days. During shutdown maintenance, all packing layers in the packing absorption section were visually and tactilely inspected to confirm that the packing showed no signs of pulverization, brittleness, deformation, or fragmentation, and that the structure was in good integrity.
[0083] Example 3
[0084] Compared to Example 1, the absorbent in this embodiment comprises the following components in parts by weight: 2.4 parts sodium persulfate, 0.17 parts hydrogen peroxide, 1.4 parts ferrous sulfate heptahydrate, and 3.7 parts EDTA; the pH of the absorbent is 4.0. EDTA and Fe... 2+ The molar ratio is 1.2:1.
[0085] The flue gas treatment capacity is 5000 Nm³. 3 / h, the original flue gas SO2 concentration is 300~500 mg / Nm 3 (Simulating low-load operating conditions).
[0086] The depth of the bubbling oxidation reaction section for absorbing the oxidation liquid layer is 0.8 m.
[0087] After the system operated continuously and stably for 180 days, the SO2 concentration at the outlet fluctuated within the range of 15~20 mg / Nm³. 3 The desulfurization efficiency is greater than 97%. Fe in the absorbent liquid 2+ -EDTA concentration fluctuation is less than 5%. S2O8 2- The average anode regeneration current efficiency was 65%, and the average H2O2 cathode generation current efficiency was 82%. The power consumption for flue gas desulfurization was 0.008 kWh / Nm³. 3 .
[0088] Example 4
[0089] Compared to Example 1, the absorbent in this embodiment comprises the following components in parts by weight: 24.0 parts sodium persulfate, 1.70 parts hydrogen peroxide, 14.0 parts ferrous sulfate heptahydrate, and 14.8 parts EDTA; the pH of the absorbent is 6.0. EDTA and Fe... 2+ The molar ratio is 1.1:1.
[0090] The flue gas treatment capacity is 5000 Nm³. 3 / h, the original flue gas SO2 concentration is 2000~2500 mg / Nm 3 (Simulating extreme high-load conditions).
[0091] The depth of the bubbling oxidation reaction section for absorbing the oxidation liquid layer is 2.0 m.
[0092] After the system operated continuously and stably for 180 days, the SO2 concentration at the outlet fluctuated between 25 and 35 mg / Nm³. 3 The desulfurization efficiency is greater than 98%. Fe in the absorbent liquid 2+ -EDTA concentration fluctuation is less than 7%. S2O8 2- The average anode regeneration current efficiency was 70%, and the average H2O2 cathode generation current efficiency was 86%. The power consumption for flue gas desulfurization was 0.018 kWh / Nm³. 3 .
[0093] Comparative Example 1
[0094] The only difference from Example 1 is that Comparative Example 1 did not include an electrochemical regeneration unit, and the Fe in the absorbent was... 2+ -EDTA complex and its oxidation product S2O8 2-Both H2O2 and SO2 are supplemented externally. Specifically, commercially available sodium persulfate solution (20 wt%) and hydrogen peroxide solution (30 wt%) are continuously added to the bubbling oxidation reaction section, with the addition amount controlled according to the inlet SO2 load at a stoichiometric ratio of 1.2. Simultaneously, 3.8 kg of FeSO4·7H2O solid is added weekly to maintain the total iron concentration in the absorbent. The remaining equipment structure, packing type, operating parameters, and detection methods are the same as in Example 1.
[0095] After the system ran continuously for 180 days, the SO2 concentration at the outlet fluctuated between 45 and 68 mg / Nm³. 3 The arithmetic mean is 56 mg / Nm 3 The desulfurization efficiency was 94.2%. Fe in the absorbent liquid... 2+ -EDTA concentration fluctuated by 18% relative to the initial value, mainly due to Fe 3+ Accumulation leads to a shift in the complexation equilibrium. The power consumption for flue gas desulfurization is 0.003 kWh / Nm³. 3 (This only covers the energy consumption of the circulating pump and fan), but the cost of the reagents, converted to the cost of treating ton of flue gas, is 0.035 yuan / Nm³. 3 The concentration was significantly higher than in Example 1. The amount of hazardous waste sludge produced was 12.5 kg / d, mainly iron sulfate sludge produced by neutralization and precipitation. During the shutdown maintenance, an inspection revealed a small amount of yellowish-brown deposits on the surface of the packing material, which felt slightly rough to the touch, but showed no obvious pulverization or brittleness.
[0096] Comparative Example 2
[0097] Compared with Example 1, the anode of the electrochemical regeneration unit in Comparative Example 2 was a Ti / RuO2-IrO2 electrode, the cathode was a graphite electrode, and all other conditions were the same as in Example 1.
[0098] After the system ran continuously for 180 days, the SO2 concentration at the outlet fluctuated between 38 and 52 mg / Nm³. 3 The arithmetic mean is 44 mg / Nm 3 The desulfurization efficiency was 96.8%. (S2O8) 2- The anodic regeneration current efficiency was only 32%, as the oxygen evolution overpotential of the Ti / RuO2-IrO2 electrode was low, and most of the current was consumed in the oxygen evolution side reaction; the H2O2 cathode generation current efficiency was 41%, but the graphite electrode corroded and peeled off in the acidic oxygen-containing environment, resulting in a continuous decrease in the effective catalytic area. 3+ The cathode reduction rate was 78%, showing a decreasing trend month by month due to cathode surface passivation. After replacing the electrode cell voltage with Ti / RuO2-IrO2, the initial cell voltage was 3.1 V, rising to 4.8 V on day 90 and reaching 5.6 V on day 180, indicating localized deactivation of the anode coating. The power consumption for flue gas desulfurization was 0.019 kWh / Nm³.3 The concentration was approximately 60% higher than in Example 1. In addition to EDTA, an extra 1.2 kg of FeSO4·7H2O was required weekly to compensate for iron loss due to insufficient cathodic reduction. The hazardous waste sludge production was 3.2 kg / day, mainly consisting of graphite electrode corrosion products and a small amount of iron precipitate.
[0099] Comparative Example 3
[0100] Compared with Example 1, the packing absorption section of Comparative Example 3 used ordinary PTFE random packing without oxidation resistance modification (commercially available standard product, without plasma grafting treatment), and all other conditions were the same as in Example 1.
[0101] After the system ran continuously for 180 days, the SO2 concentration at the outlet was maintained at 30-35 mg / Nm³ for the first 60 days. 3 The desulfurization efficiency was greater than 99%; the SO2 concentration at the outlet gradually increased from day 61, and by day 180, the fluctuation range had increased to 58~82 mg / Nm³. 3 The arithmetic mean is 69 mg / Nm 3 The desulfurization efficiency dropped to 91.5%. During the shutdown for maintenance, the packing material was removed for observation. It was found that the surface of the packing material was noticeably white and lacked luster; it crumbled easily when squeezed, with a fragmentation rate of approximately 35%. The pressure drop across the packing layer increased by 2.4 times compared to the initial value, indicating that the packing material had undergone severe aging and brittle fracture after prolonged immersion in the highly oxidizing absorbent. The water contact angle of the PTFE packing material increased from the initial value of 98° to 126°, indicating a complete loss of hydrophilicity and a significant reduction in the gas-liquid mass transfer interface. Fluoride ions produced by PTFE degradation were detected in the absorbent, with a concentration of 8.6 mg / L, confirming that the packing material itself had undergone chemical corrosion.
[0102] Comparative Example 4
[0103] Compared with Example 1, in Comparative Example 4, NaCl of equimolar concentration was used instead of EDTA as the supporting electrolyte in the absorbent solution, no organic complexing agent was added, and all other conditions were the same as in Example 1.
[0104] After the system ran continuously for 180 days, the SO2 concentration at the outlet was measured during the initial 14 days of operation, which was 32-38 mg / Nm³. 3 The desulfurization efficiency was greater than 98%; the SO2 concentration at the outlet rose rapidly from day 15, reaching 95-120 mg / Nm³ by day 30. 3 The desulfurization efficiency dropped below 82%, forcing the system to shut down. Post-shutdown sampling and analysis revealed free Fe in the absorbent liquid. 3+ Concentration as high as 1.8 g / L, Fe 2+ The concentration is below the detection limit, indicating that the iron catalyst is almost entirely composed of Fe. 3+ Speciation deactivation; Fe 3+The cathodic reduction rate had decreased to 22% by day 14 and could not be effectively measured thereafter. The pH of the absorbent spontaneously decreased from an initial 5.2 to 2.8, due to Fe... 3+ This is due to acid production from hydrolysis. A reddish-brown layer of ferric hydroxide scale covered the cathode surface of the electrochemical regeneration unit, causing the cell voltage to rise from 4.2 V to 7.8 V, essentially resulting in the loss of regeneration function. This comparative example demonstrates that, without the protection of a multidentate organic complexing agent, the iron catalyst cannot maintain its dissolved activity in a weakly acidic absorbent solution with a pH of 4.0–6.0.
[0105] The above description is merely some specific embodiments of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for desulfurization of waste incineration flue gas based on oxidation absorption, characterized in that, Includes the following steps: Step 1: Rapidly cool the flue gas from waste incineration to 70-90°C; Step 2: The cooled flue gas is sprayed and washed with alkaline solution to remove fly ash and acidic gases, and the Cl content in the flue gas after washing is controlled. - With a concentration <500 mg / L, pre-washed flue gas was obtained; Step 3: The pre-washed flue gas is passed from bottom to top through the main absorption tower (1), sequentially passing through the bubbling oxidation reaction section (2), the packed absorption section (3), and the spray washing section (4) within the main absorption tower (1). The absorbent liquid flows from the main absorption tower (1) sequentially through the spray washing section (4) and the packed absorption section (3) into the absorbent oxidation liquid layer of the bubbling oxidation reaction section (2), causing the SO2 in the flue gas to dissolve in the absorbent liquid and be dissolved by persulfate and hydrogen peroxide in the Fe... 2+ The sulfate and hydroxyl radicals generated under catalysis are oxidized in situ to SO4. 2- The flue gas is purified. Step 4: The absorbent in the oxidizing liquid layer is passed into the electrochemical regeneration unit, which includes an anode chamber and a cathode chamber separated by an ion exchange membrane. The absorbent enters the anode chamber and the cathode chamber respectively. The anode chamber uses a high oxygen evolution overpotential anode to remove SO42- from the absorbent. 2- Oxidation and regeneration to persulfate; the cathode chamber uses a carbon-based cathode, and oxygen-containing gas is continuously introduced into the cathode chamber, where Fe in the absorbent liquid is absorbed. 3+ Reduction and regeneration to Fe 2+ At the same time, the O2 in the oxygen-containing gas is reduced to H2O2 in situ; the absorbent liquids after the reaction in the anode chamber and cathode chamber are combined and returned to the upper end of the main absorption tower (1) for recycling.
2. The method for desulfurization of waste incineration flue gas based on oxidation absorption according to claim 1, characterized in that, The absorbent comprises the following components in parts by weight: 2.4-24.0 parts sodium persulfate, 0.17-1.70 parts hydrogen peroxide, 1.4-14.0 parts ferrous sulfate heptahydrate, and 3.7-18.6 parts multidentate complexing agent; the pH of the absorbent is 4.0-6.
0.
3. The method for desulfurization of waste incineration flue gas based on oxidation absorption according to claim 1, characterized in that, The multidentate complexing agent is EDTA or EDDS; when the multidentate complexing agent is EDTA, its weight fraction is 3.7~14.8 parts; when the multidentate complexing agent is EDDS, its weight fraction is 4.5~18.6 parts; the multidentate complexing agent and Fe 2+ The molar ratio is 1:1 to 2:
1.
4. The method for desulfurization of waste incineration flue gas based on oxidation absorption according to claim 1, characterized in that, The bubbling oxidation reaction section (2) includes a gas distributor immersed in the absorption oxidation liquid layer; after the pre-washed flue gas passes through the gas distributor, the flue gas is a microbubble with an average diameter of ≤3mm.
5. The method for desulfurization of waste incineration flue gas based on oxidation absorption according to claim 1, characterized in that, The packing absorption section (3) is provided with at least two sections of oxidation-resistant modified packing layers, and an annular groove liquid redistribution structure (10) is provided between two adjacent oxidation-resistant modified packing layers; the oxidation-resistant modified packing layers include one of the following: surface hydrophilic modified polytetrafluoroethylene packing, polyvinylidene fluoride packing or silicon carbide packing.
6. The method for desulfurization of waste incineration flue gas based on oxidation absorption according to claim 1, characterized in that, In step 4, the electrochemical regeneration unit includes an electrolytic cell divided into an anode chamber and a cathode chamber by an ion exchange membrane; the absorbent enters the anode chamber and the cathode chamber respectively, and after the reaction, they are combined and returned to the main absorption tower (1). The anode includes one of a boron-doped diamond electrode, a Ti / SnO2-Sb electrode, or a Ti / PbO2 electrode; the cathode includes one of a graphite felt, a carbon felt, or a carbon nanotube-modified electrode.
7. The method for desulfurization of waste incineration flue gas based on oxidation absorption according to claim 4, characterized in that, The depth of the absorption oxidation liquid layer in the bubbling oxidation reaction section (2) is 0.8~2.0m, and the microbubbles formed after the pre-washed flue gas passes through the gas distributor have a residence time of ≥5s in the absorption oxidation liquid layer.
8. The method for desulfurization of waste incineration flue gas based on oxidation absorption according to claim 1, characterized in that, In step 4, oxygen-containing gas is continuously introduced into the cathode chamber of the electrochemical regeneration unit. The oxygen-containing gas is oxygen-enriched air with an oxygen volume fraction of 25% to 40%. The oxygen-containing gas is introduced through a microporous aeration disc at the bottom of the cathode chamber, and the apparent gas velocity is controlled to be 0.5 to 3.0 cm / s.
9. A waste incineration flue gas desulfurization system based on oxidation absorption, used to implement the method according to any one of claims 1-8, characterized in that, It includes a quench tower, a pre-washing tower and a main absorption tower (1) connected in sequence along the flue gas flow direction. The main absorption tower (1) is connected to the electrochemical regeneration unit through a circulation pipeline. The main absorption tower (1) is divided into a bubbling oxidation reaction section (2), a packing absorption section (3), and a spray washing section (4) from bottom to top. The bubbling oxidation reaction section (2) is located at the bottom of the main absorption tower (1). An absorption oxidation liquid layer is provided in the bubbling oxidation reaction section (2). The bubbling oxidation reaction section (2) includes a gas distributor immersed in the absorption oxidation liquid layer. The gas distributor includes a microporous distributor (6) and a macroporous distributor (5) arranged sequentially from top to bottom. At least two oxidation-resistant modified packing layers are provided in the packing absorption section (3), and an annular groove liquid redistribution structure (10) is provided between two adjacent oxidation-resistant modified packing layers. The electrochemical regeneration unit includes an electrolytic cell divided into an anode chamber and a cathode chamber by an ion exchange membrane. The anode chamber is equipped with a high oxygen evolution overpotential anode, and the cathode chamber is equipped with a carbon-based cathode. The bottom of the cathode chamber is provided with a microporous aeration disc. The spray washing section (4) is provided with a spray layer for washing the flue gas.
10. A waste incineration flue gas desulfurization system based on oxidation absorption according to claim 9, characterized in that, The spray layer includes a first spray layer (11), a second spray layer (12) and a third spray layer (13) arranged sequentially from bottom to top; the spray pressure of the first spray layer is 0.3~0.5MPa and the average particle size of the atomized droplets is 100~200μm; The second spray layer uses swirling nozzles, with an average droplet size of 80~150μm; The third spray layer uses fine atomizing nozzles, with an average droplet size of 50~100μm.
